Tinjauan Maslahah Mursalah terhadap Fenomena Childfree - Salahuddin, Citra Widyasari; Hidayat, Taufiq (DIKTUM: Jurnal Syariah dan Hukum, 2022)
Childfree became a popular term after entering the 21st century. The child-free phenomenon does not only occur in developed countries such as Europe, but also in developing countries such as Indonesia. This study seeks to examine childfree from various perspectives and then find its legal limits in Islam. Efforts to find the limits of child-free law in Islam are carried out using the maslahah mursalah theory. The research is included in library research with data material derived from secondary data including literature related to the theme of Childfree and maslahah mursalah theory. The results show that in general, the choice of child-free is due to career reasons, the desire to live alone with a partner and financial considerations. So according to the concept of al-Daruriyat Imam Al-Gazali, this reason does not meet the qualifications of maslahah daruriyat. On the other hand, the Qur'an and hadith recommend having children, so that it is supported by syara'. In other words, not having children because the choice (childfree) is against the will of syara' or the law is makruh.